Pemetaan Skenario Genangan Tsunami Berbasis Pemodelan Spasial - Adip Wahyudi; Anggit Priadmodjo; Adi Aksa; Finda Aulia Islaha (Jurnal Penelitian Pendidikan Geografi, 2024)
This research uses a spatial modeling approach to map tsunami inundation scenarios in Majene Regency, West Sulawesi Province utilizing topographic data, bathymetry, and other related information. This research aims to design a model that can visualize potential inundation and affected areas along the coastline of Majene Regency with 6 meter, 10 meter, and 30 meter inundation scenarios. This modeling analysis provides an in-depth picture of the potential impact of the tsunami disaster, especially on all sub-districts in Majene Regency. The modeling results are made into three classifications: high, medium, and low. The modeling results show that the sub-districts have a hazard index and tsunami inundation area in the high category for the 6, 10, and 30-meter scenarios Malunda and Sendana sub-districts. The sub-districts that have a hazard index and tsunami inundation area in the medium variety for the 6, 10, and 30 meter scenarios are Banggae, East Banggae, Pamboang, Tammerodo Sendana, and Tubo Sendana sub-districts. The sub-district that has a hazard index and tsunami inundation area in the low category for the 6, 10, and 30-meter scenarios is Ulumanda Subdistrict.